Graphene reinforced radiation crosslinked polyvinyl alcohol/carboxymethyl cellulose nanocomposites for controlled drug release. (9th October 2015) - Guin, Jhimli P.; Chaudhari, C.V.; Dubey, K.A.; Bhardwaj, Y.K.; Varshney, L.
Abstract : This study reports development of graphene reinforced nanocomposites of carboxymethyl cellulose and polyvinyl alcohol for controlled drug release applications. The nanocomposites were synthesized through solution blending coupled with sonication assisted dispersion. The matrices were crosslinked to different extent by imparting different high energy radiation doses. The elastic modulus of the polymer nanocomposites increased by fourfold with the increase in graphene content from 1 to 3 wt% with no further significant change in elastic modulus at higher graphene content. The crystalline content did not change with addition of graphene and was ∼40% for all nanocomposites. Addition of 3 wt% graphene marginally increased the time for 60% drug release ( T 60 ). However, T 60 increased by ∼100% with an increase in radiation dose from 25 to 150 kGy, suggesting absorbed radiation dose to be a critical factor for graphene based nanocomposites for controlled drug release applications. POLYM. COMPOS., 38:E74–E80, 2017. © 2015 Society of Plastics Engineers